Optimal capacitor allocation for power transfer capability and power loss improvements in power transmission systems using evolutionary programming - Srisathian,P. (2015)
Capacitor allocation in power transmission systems have been considered to improve voltage profile and reduce power loss. An evolutionary programming (EP) is a computationally efficient methodology for the optimal capacitor allocation in power transmission network. The method is chosen due to its robustness and its ability to handle many practical constraints, explore all possible solutions, and find optimal solution within reasonable time. This method is proposed to determine the optimal allocation of capacitor for maximizing the total transfer capability (TTC) and minimize power loss by focusing on cost of capacitors and max TTC in systems. © 2011 IEEE.